Pengaruh TIk, Investasi Asing dan Pendidikan terhadap Kemiskinan di Indonesia - alya erlina afiah; Ariusni (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study aims to analyze the effect of Information and Communication Technology (ICT), Foreign Direct Investment (FDI), and Education on poverty levels in Indonesia. The research employs panel data from 34 provinces in Indonesia over the period 2009–2023 and applies the Fixed Effect Model (FEM) as the analytical method. The results show that both ICT and FDI have a negative and significant effect on poverty. This indicates that improvements in ICT access and inflows of foreign investment can reduce poverty levels through job creation, productivity growth, and economic efficiency. Conversely, education has an insignificant effect on poverty, implying that there is still a gap between the quality of education and the needs of the labor market in Indonesia. Simultaneously, ICT, FDI, and education jointly have a significant influence on poverty. These findings highlight the importance of synergy among digital development, productive investment, and human resource improvement to achieve inclusive and sustainable economic growth.